Implimentation of the Sustainable Development Goals in Belarus: an Agenda until 2030 - Shchetkina, Marianna A.; Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted to analyzing the implementation of sustainable development goals in Belarus. The Agenda until 2030, which contains 17 Sustainable Development Goals that form the image of the future world, is presented. The Republic of Belarus has begun work on the implementation of the Sustainable Development Goals at the national level, relying on the key documents – the National Strategy for Sustainable Socio-Economic Development of the Republic of Belarus for the period until 2030 and the Program for Social and Economic Development of the Republic of Belarus for 2016–2020. The concept of a national strategy was formulated and discussed at the first National Forum on Sustainable Development (Minsk, 24 January 2019), which formulated specific measures for the implementation of the Agenda-2030.
Keywords: Republic of Belarus; Agenda-2030; Sustainable Development Goals; National Forum on Sustainable Development; National Strategy Concept